A Deep Heat Recovery Device between Flue Gas and Supply Air of Gas-fired Boiler by Using Non-contact Total Heat Exchanger. (May 2017) - Chen, Wei; Shi, Wenxing; Wang, Baolong; Shang, Sheng; Li, Xianting
Abstract: The flue gas of boiler contains large amount of waste latent heat, and traditional heat recovery device is difficult to recover the latent heat due to the limitation of the specific heat of supply air. A deep heat recovery device between flue gas and supply air of gas-fired boiler is proposed in the paper, and the thermodynamic model is established to calculate its performance. The energy efficiency of gas-fired boiler with the device is compared with other systems. The result shows that the boiler efficiency with new heat recovery device is 5% and 13% higher than that of condensing boiler and boiler without heat recovery system, respectively. When the ambient temperature is higher, the energy efficiency is closer to the boiler with absorption heat pump for heat recovery, and the initial investment is lower. Therefore, both the energy efficiency and economy of this system is acceptable.